معوقات الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة بمحافظة دمياط - الفار، رنا حامد; جوهر، علي صالح حامد; جمعة، محمد حسن أحمد (جامعة دمياط - كلية التربية, 2022)
تعد قضية الشراكة بين المدارس الدامجة وأولياء أمور الأطفال ذوي الإعاقة بتلك المدارس من القضايا الحيوية والتي لم تتناولها الأدبيات التربوية بشكل تفصيلي مما يدلل على أن هذا البعد لم ينل الاهتمام الكافي في مجال الدراسات التربوية المعاصرة. هدف البحث إلى: إبراز الإطار المفاهيمي للمدارس الابتدائية الدامجة في مصر. واستعراض الأسس العامة لتعزيز الشراكة بين أولياء الأمور والمدارس الابتدائية الدامجة. ورصد أهم المعوقات التي تواجه الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة بمحافظة دمياط. والتوصل لآليات دعم الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة بمحافظة دمياط. منهج البحث اعتمد البحث على المنهج الوصفي. نتائج البحث: توصل البحث إلى آليات تفعيل دور الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة بمحافظة دمياط، وتتمثل في: - إدراك الفوائد المتوقعة من الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة في النهوض بالعملية التعليمية. - الاستفادة من التجارب والخبرات المحلية والعالمية في الشراكة بين المدارس الابتدائية الدامجة وأولياء أمور الأطفال ذوي الإعاقة. - انتهاج سياسة تسويقية اجتماعية لبرامج وأنشطة المدارس الابتدائية الدامجة بما يمكنها من تعزيز الشراكة مع المجتمع - بناء مناخ دائم وإيجابي للعمل التطوعي والاستفادة من التجارب الناجحة واستثمارها - تدريب أعضاء مجالس الأمناء والأباء والمعلمين على أساليب تحقيق الجودة الشاملة في التعليم - تشجيع وزارة التربية والتعليم أولياء أمور الأطفال ذوي الإعاقة على الشراكة الفعالة من خلال رفع الوعي بأهميتها. The partnership between mainstream schools and parents of children with disabilities at these schools is considered one of the vital issues which is not covered in detail in the educational literature, and that means this dimension didn't get enough attention in the field of contemporary educational studies. The aim of the research: Determining the conceptual framework of mainstream primary schools in Egypt, reviewing the general basis of increasing the partnership between parents and mainstream primary schools, monitor the main constraints facing the partnership between the primary mainstream schools and parents of children with disabilities in Damietta and concluding with dimensions of supporting the partnership between mainstream primary schools and parents of children with disabilities in Damietta. Methodology of the research: The research depend on the descriptive approach. Results of the research: The research concluded with dimensions of activating the role of partnership between primary mainstream schools and parents of children with disabilities in Damietta as the following: - Realizing the expected benefits from partnership between the primary mainstream schools and parents of children with disabilities in promotion of the educational process. - Taking advantage from the national and international experiences and experiments in partnership between primary mainstream schools and parents of children with disabilities. - Social marketing policy for programs and activities of primary mainstream schools to enable it from promoting the partnership with society. - Building positive and a permanent atmosphere for volunteer work and benefit from successful experiments and investing it. - Training of members of the boards of trustees, parent and teachers on the methods of achieving the total quality in education. - Encouraging the parents of children with disabilities by the ministry of education on the active partnership through raising consciousness of its importance.
Keywords: الإدارة التربوية -- التربية الخاصة -- المشاركة المجتمعية -- الشراكة الأسرية -- التعلم المدمج